Debating Islam in the Jewish state : the development of policy toward Islamic institutions in Israel - Peled, Alisa Rubin, 1965- (SUNY series in Israeli studies., 2001)
Drawing on Israeli archival documents, Peled (public policy and administration, Ben-Gurion U. of the Negev) studies the history of jurisdictional conflicts over Muslim affairs in Israel. Includes photos of minority affairs officials and Islamic Movement protesters. Appends information on Shari'a courts and the UN role in Jerusalem. c. Book News Inc.